Estudo comparativo de frameworks e arquiteturas para desenvolvimento escalável de servidor de jogos educacionais - Garcia, Lucas Gabriel Schumann (2023)
The Federal Tecnological University of Paraná is developing - through an extension project, educacional gams to teach arithmetic and basic operations. The games have a playful and interactive approach, using elementes od eletronic games to maintain students` interest and motivation. In this scenario, somo common problems arise related to game communication interfaces: usage overlord and synchronous communications. Seeking to slove the problem of high rate of requestes in a system and guarantee its scalability, this proposal will involve a comparative study oriented to tests, to find an architecture, data modeling and appropriate application server configuration, valuing mainly the availability and agility. In this work, performance tests were carried out, based on response time, on each selected tool, wich resulted in greater efficiency with the non-relational MongoDB base and whih the EJB component for API. The work also includes a collection of duly documented information on data structures databases and other tested tools. The development of the work brings a series of defined guidelines and recomendations, with theorical and practical content, that can be used in the system.